The Problematics Mitigation of Forest and Land Fire District (Kerhutla) in Policy Perspective (A Case Study : Kalimantan and Sumatra in Period 2015-2019) - Sarmiasih, Mia; Pratama, Prawira Yudha (Journal of Governance and Public Policy, 2019)
Forests are the source of community life. In recent years the problem of natural disasters in forest fires (Kerhutla) in two provinces in Kalimantan and Sumatra has been very detrimental to the state and local communities. Disasters are events that can be social, economic and political. Based on the results of this study it can be concluded that forest fires compared to 2015 and 2019, the largest forest and land burning was in 2015, which is the largest forest and burning area of around 2.6 million hectares. Meanwhile, in 2019 forest and land fires will reach 328,722 hectares. On average, forest fires are caused by humans such as land clearing and illegal logging, land clearing usually occurs every year, but this time the forest fires are organized. they are irresponsible parties who deliberately ride local communities to intentionally commit forest fires. In this study, research is analyzed through state-centric and communal analysis and market-based dynamics. The result is when viewed from the state-centric that the State through its governmental institutions has issued several policies at the national level to the local level while these countries are invited to participate in international cooperation to reduce and minimize fires. If viewed from a communal analysis that forest fires are not free from the surrounding culture. This is evidenced by the tradition claimed every year to open land for settlements. Apart from illegal logging and when viewed from a Market Based analysis that forest fires are precisely caused by companies that play to their advantage. In the case of forest and land fires, there is actually an interest to be achieved from forest and land fires. There is some data that results that there is political competition by the local political elite so that the forest fires occur. Forest fires will continue if the government cannot provide strict laws to irresponsible parties. The state must be present as a tool to control its citizens so as not to burn forests and land that harms the country.